State-Corporate Crime and Social Harm in the Spanish Crisis. (1st October 2014) - Camilo Bernal; Alejandro Forero; Iñaki Rivera
Abstract : Since 2008, Spain has been facing a deep economic and financial crisis, which has generated significant levels of social harm among its inhabitants. This article highlights the destructive connections which exist between the financial crisis and state-corporate crimes; specifically, it focuses upon the criminal symbiosis between private banking and political power, in the contexts of both the state's financial crisis and in the participation of private banking in financing the Spanish military industry.